PENGARUH REVIEW PRODUK DAN KUALITAS PRODUK TERHADAP MINAT BELI PRODUK SKINCARE SKINTIFIC PADA MAHASISWA KAMPUS II BANJARBARU UNIVERSITAS ACHMAD YANI BANJARMASIN - Jumiati; Adha Fithriani; Indah Fitriastuti (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
The purpose of this research is to determine, analyze, and prove the partial effect of product reviews on purchase intention, the partial effect of product quality on purchase intention, and the simultaneous effect of product reviews and product quality on the purchase intention of Skintific skincare products among students at Campus II Banjarbaru, Universitas Achmad Yani Banjarmasin. The research variables are divided into three variables: product reviews (X1), product quality (X2), and purchase intention (Y). The type of research is quanti¬tative descriptive analysis. Data collection techniques include observation, interviews, literature review and dis¬tributing questionnaires. The population in this study consists of 87 students, with a sample size of 71 students. The analysis technique in this research uses multiple linear regression method. The results of the multiple linear regression are Y = 2.019 + 0.055 X1 + 0.740 X2 + e. Product reviews have no partial effect on purchase inten¬tion, as t-count < t-table, which is 0.380 < 1.994, and the significance value is 0.705. Product quality has a par¬tial effect on purchase intention, as t-count > t-table, which is 9.880 > 1.994, and the significance value is 0.000. Product reviews and product quality have a simultaneous effect on purchase intention, as F-count > F-table, which is 79.107 > 3.13, and the significance probability is < 0.05, which is 0.000. The adjusted R-squared value of 0.691 means that the ability of the Product Review variable (X1) and Product Quality variable (X2) can ex¬plain the Purchase Intention variable (Y) by 69.1%, while the remaining 30.9% is explained by other variables.